Kawasaki Disease with an Initial Manifestation Mimicking Bacterial Inguinal Cellulitis - Tsukasa Tanaka; Masaki Shimizu; Oshi Tokuda; Hiroko Yamamoto; Natsuki Matsunoshita; Kanae Takenaka; Keiichiro Kawasaki (Case Reports in Pediatrics)
Background. Kawasaki disease (KD) is typically characterized by fever, oral cavity erythematous changes, bilateral bulbar conjunctival injection, skin rash, erythema and edema of the hands and feet, and cervical lymphadenopathy. Some atypical patients with KD initially develop cervical and pharyngeal cellulitis; however, an initial presentation with inguinal cellulitis is extremely rare. In addition, to our knowledge, no report has documented the cytokine profile in a KD patient with cellulitis. Case presentation. A previously healthy 8-year-old Japanese girl was hospitalized following a 2-day history of fever and a 5-day history of pain and erythema in the left inguinal region. She was diagnosed with bacterial inguinal cellulitis and was administered antibiotics. The next day, a polymorphous rash emerged on her trunk. After 3 days of antibiotics, however, her fever continued and the cellulitis had spread over the entire lower abdomen. Simultaneously, the bilateral bulbar conjunctival injection without exudate became more prominent and her lips became erythematous. In addition, erythematous changes on her palms appeared a few hours later, which led to the diagnosis of KD. Since she had a high risk score that predicted no response to initial intravenous immunoglobulin (IVIG) at the initiation of treatment, she was treated with IVIG, intravenous prednisolone (PSL), and oral aspirin. The KD symptoms improved the next day, but the cellulitis did not completely resolve until 2 months after discharge. The patient’s serum cytokine profile at admission had an IL-6 dominant pattern which was consistent with that of patients with KD despite her initial lack of KD symptoms, and the pattern observed at admission was sustained until IVIG and PSL administration. Conclusion. KD should be included in the differential diagnosis for patients presenting with inguinal cellulitis who are unresponsive to initial empiric antibiotics.